1985
DOI: 10.1002/ana.410180603
|View full text |Cite
|
Sign up to set email alerts
|

Positron emission tomographic measurement of blood‐to‐brain and blood‐to‐tumor transport of 82Rb: The effect of dexamethasone and whole‐brain radiation therapy

Abstract: Unidirectional blood-to-brain and blood-to-tumor transport rate constants for rubidium 82 were determined using dynamic positron emission tomography in patients with primary or metastatic brain tumors. Regional influx rate constants (K1) and plasma water volume (Vp) were estimated from the time course of blood and brain radioactivity following a bolus injection of tracer. Eight patients were studied before and 24 to 72 hours after treatment using pharmacological doses of dexamethasone, and 6 additional patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
1

Year Published

1987
1987
1996
1996

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(42 citation statements)
references
References 35 publications
2
39
1
Order By: Relevance
“…Consequently, the mean K of tumor in the present patient study (both before and after treatment) was about 3 times higher than the two values cited above. The decrease in tumor K after dexamethasone therapy in this study agreed with the data measured with 82Rbt and PET [2,3]. Our data support the view that corticosteroids decrease the tumor capillary permeability to small hydrophillic molecules and hence have an antiedema effect.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consequently, the mean K of tumor in the present patient study (both before and after treatment) was about 3 times higher than the two values cited above. The decrease in tumor K after dexamethasone therapy in this study agreed with the data measured with 82Rbt and PET [2,3]. Our data support the view that corticosteroids decrease the tumor capillary permeability to small hydrophillic molecules and hence have an antiedema effect.…”
Section: Discussionsupporting
confidence: 93%
“…Nakagawa et al [1] showed that dexamethasone reduced the K of 125I Albumin and Vp in RG-2 glioma in rats. Jarden showed a time course of reduction in K of 82+Rb and Vp in human brain tumors at 6 and 24 hours after intravenous injection of dexamethasone using positron emission tomography (PET) [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Although this 'vasogenic' cerebral edema can be reduced or controlled to some extent by corticosteroid medications, tumor-associated edema remains a major cause of morbidity and mortality [14,22,33]. Dexamethasone and methylprednisolone are the most commonly used steroids in the neurosurgical setting [4] and, while their exact mechanism of action on cerebral edema is unclear, it has been postulated that they decrease blood-brain and blood-tumor vascular permeability, constrict cerebral vessels, alter transport of sodium, potassium, and water across the endothelial plasmalemma or capillary-glial interface, and stabilize lysosomal membranes [14,21,24,45]. Also, by reducing the extracellular space in the tumor and adjacent brain, steroids indirectly increase the resistance to fluid flow through the brain, reducing the convective spread of plasma-derived edema fluid.…”
Section: Discussionmentioning
confidence: 99%
“…These are glucocortieoid receptors in botch normal brain [2] and brain tumors [3,4]. Among the published effects o f corticosteroids on brain tumors must be listed changes in cellular proliferation [5], tumor blood flow [6], tumor capillary permeability [7] and energy metabolism [6,8], besides the well known reduction of tumor-associated brain edema [1]. The numerous biological perturbations caused by corticosteroids make it difficult to interpret experimentalobservations in terms of a direct effect on a single biological process.…”
Section: Tnlroauctlonmentioning
confidence: 99%